Investigation into the Effect of Fibre Geometry on the Performance of Macro Synthetic Fibre Reinforced Concrete - Lerch, Jean Oliver (Stellenbosch : Stellenbosch University, 2016)
Thesis (MEng)--Stellenbosch University, 2016.